Longitudinal-radial motion of an electron beam in the solenoidal field of the secundary-emission magnetron gun - Dovbnya, A.N.; Dovbnya, N.A.; Mazmanishvili, А.S.; Reshetnyak, N.G. (Вопросы атомной науки и техники, 2017)
The results of experimental studies and numerical calculations on the generation of an electron beam by a magnetron gun with a secondary-emission cathode are presented. With the aim of obtaining precision characteristics, the formation of a beam in the axial and radial directions was studied when transporting a solenoid in a magnetic field at energy of 55 keV. The dependence of the total vertical distribution on the inner wall of the cylindrical target and the Faraday cylinder on the distribution of the magnetic field along the axis of the system is studied. The results of nu-merical simulation on the motion of a tubular electron beam are given. It is shown that the obtained results of the simulation are consistent with experimental data. It is also shown that the electron flux falls on a vertical section, the length of which does not exceed 1 mm. The possibility of adjusting the location of a beam hit on a vertical wall is studied numerically with a variation in the amplitude of the control magnetic field.